A Critique of Laser-Induced Incandescence for the Measurement of Soot - Smallwood , Gregory J. (Cranfield University, 2008)
The health and environmental risks due to airborne nanoparticles are important issues facing the citizens and governments of the industrialized countries. To assess and mitigate these risks, increasingly stringent regulations are being enacted to reduce the particulate emissions from the combustion of hydrocarbon fuels, which primarily consist of soot. Improvements to the understanding of the formation of soot nanoparticles and their impact on the health and the environment are required. This necessitates advances in the state of quantitative measurement of soot. Laser-induced incandescence (LII) is an optical diagnostic technique for the measurement of concentration and primary particle diameter of soot with high selectivity. Limitations with conventional LII were identified and a significantly enhanced technique, autocompensating LII (AC-LII), was developed employing time- resolved two-colour pyrometry, low fluence, and an absolute intensity calibration to address these limitations. AC-LII was shown to measure the soot particle temperature and automatically compensate for variations in the measurement environment that affected the peak soot particle temperature. With low fluence, AC-LII was shown to avoid soot sublimation, which impacted the measurements of concentration and size with high fluences. AC-LII was applied to flames and to combustion-generated emissions. At low ambient temperatures it was discovered that the measured concentration varied with fluence. To mitigate this issue, it was recommended that AC-LII be performed at a moderate fluence near the sublimation threshold. In order to assess the impact of distributions of the soot primary particle diameter and of aggregate size, analysis coupling experiments with a state-of-the-art numerical model of the heat transfer was performed. The results showed that AC-LII signal evaluation should begin immediately after an initial anomalous cooling period but before distribution effects become dominant. The sensitivity of AC-LII was optimized and applied to measure atmospheric black carbon concentrations. Comparison to other instruments demonstrated that AC-LII has significant advantages for the measurement of soot, and represents a major advancementin techniques for nanoparticle characterization.